2010
DOI: 10.1088/0031-9155/55/9/003
|View full text |Cite
|
Sign up to set email alerts
|

The clinical feasibility of deep hyperthermia treatment in the head and neck: new challenges for positioning and temperature measurement

Abstract: To apply high-quality hyperthermia treatment to tumours at deep locations in the head and neck (H&N), we have designed and built a site-specific phased-array applicator. Earlier, we demonstrated its features in parameter studies, validated those by phantom measurements and clinically introduced the system. In this paper we will critically review our first clinical experiences and demonstrate the pivotal role of hyperthermia treatment planning (HTP). Three representative patient cases (thyroid, oropharynx and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 36 publications
1
68
0
Order By: Relevance
“…This facilitates treatment planning by developing treatment-planning software as a Web application, which allows remote generation of treatment plans (Olsen et al 2000). Moreover, the treatment-planning software should be as automated as possible since without treatment-planning software a clinician (i.e., a medical doctor) may otherwise need about 6 h to manually perform segmentation of a patient (Paulides et al 2010). The advance from treating skin metastases to treating deep-seated tumors would be facilitated by userfriendly treatment-planning software that would allow clinicians to prepare patient-specific treatment plans without the need of an engineer or a medical physicist or specialized engineering knowledge (Pavliha et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates treatment planning by developing treatment-planning software as a Web application, which allows remote generation of treatment plans (Olsen et al 2000). Moreover, the treatment-planning software should be as automated as possible since without treatment-planning software a clinician (i.e., a medical doctor) may otherwise need about 6 h to manually perform segmentation of a patient (Paulides et al 2010). The advance from treating skin metastases to treating deep-seated tumors would be facilitated by userfriendly treatment-planning software that would allow clinicians to prepare patient-specific treatment plans without the need of an engineer or a medical physicist or specialized engineering knowledge (Pavliha et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments performed thus far have shown the feasibility of deep heating by a non-invasive technique using microwaves [16]. Furthermore, we showed that intratumoural temperature measurements in the nasopharynx are challenging but feasible.…”
mentioning
confidence: 88%
“…It is mostly used to treat deep tumors like pelvis or abdomen. This method is more complex than the first one, because of the complexity and nonhomogeneity of the targeted region [39].…”
Section: Regional Hyperthermiamentioning
confidence: 99%
“…Another method exists based on the use of embedded thermal sensors to measure the temperature. The probe or the invasive heating source is equipped with sensors to measure the temperature locally [2,32,36,39].…”
Section: Challenges Of Hyperthermiamentioning
confidence: 99%